Beyond Charisma: A Weberian Analysis of Internal Conflict Resolution Mechanisms in Early Nigerian Pentecostalism - Caleb Adeleye; Oluwasegun Aluko (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2026)
This study applies Max Weber’s theory of authority, with particular attention to the routinisation of charisma, to examine how early Nigerian Pentecostal movements managed internal disputes during their formative decades. Moving beyond narratives that privilege revival intensity and charismatic personality, the paper foregrounds the socio-historical mechanisms (formal and informal) through which early Pentecostal communities addressed doctrinal disagreements, leadership contestation, and tensions over public order, sacred space, and relations with traditional institutions. Using episodes drawn primarily from the early history of The Apostolic Church Nigeria (TACN) and the schismatic pathways that contributed to the consolidation of the Christ Apostolic Church (CAC) communities in Southwestern Nigeria, the analysis shows that conflict resolution was not merely reactive. It functioned as a formative governance practice through which legitimacy was negotiated, boundaries were drawn, and organisational continuity was secured. By reading conflict episodes as sites where charismatic authority was translated into procedures, offices, and territorially anchored institutions, the study offers a conflict-centred account of Pentecostal institutionalisation and highlights the often-unseen organisational labour underpinning the public visibility of Nigerian Pentecostalism.